Lockdown leading obesity and its possible impacts on the second wave of COVID-19 - Siddiqui, Shafayet Ahmed; Md Jakaria, - (Bangladesh Journal of Medical Science, 2020)
Abstract not available Bangladesh Journal of Medical Science Vol.19(0) 2020 p. S 101-S 102